Novel Multicomponent Anticancer Combinations and Their Potentiation with Copper Oxide Nanoparticles: Selective Cytotoxicity Against A549 Cells - Archil Chirakadze; Nodar Mitagvaria; Nelly Makhviladze; Mari Razmadze; Teimuraz Chubinishvili; Zakaria Buachidze; Irina Khomeriki; Fareeha Aziz Mengal; Mohammed Afnaan Ahmed; Anushka Rohidas Temgire; Akshay Sajeev; Nora Thing; et al. (Interdisciplinary Science Studies, 2025)
The development of selective and less toxic anticancer therapies remains a significant challenge in oncology. In this study, four novel multicomponent anticancer combinations were evaluated against human lung cancer A549 cells and compared with normal human dermal fibroblasts (NHDF). Cell proliferation and cytotoxicity were assessed using MTT assay, while apoptosis induction was evaluated via Annexin V-FITC/PI flow cytometry. Results demonstrated that all four combinations exerted marked cytotoxicity in A549 cells with limited effects on NHDF, in contrast to standard chemotherapeutics cisplatin and gemcitabine, which showed higher toxicity towards normal cells. Among the tested agents, sample 1 exhibited the most potent anticancer effect with the highest safety index. Furthermore, potentiation with copper oxide (CuO) nanoparticles significantly enhanced cytotoxicity and apoptotic induction, indicating a synergistic interaction and improved selectivity. These findings suggest that the tested combinations, particularly when formulated with CuO nanoparticles, represent promising candidates for further preclinical evaluation as safe and effective anticancer therapeutics.